Erratum to “Small molecule inhibitors of mammalian glycosylation” [Matrix Biol. Plus 16C (2022) 100108] (Matrix Biology Plus (2022) 16, (S2590028522000084), (10.1016/j.mbplus.2022.100108)) - Almahayni, Karim; Spiekermann, Malte; Fiore, Antonio; Yu, Guoqiang; Pedram, Kayvon; Möckl, Leonhard (Matrix Biology Plus, 2022)
This article was temporarily removed in April 2022 due to production errors by the publisher. The publisher apologizes for any inconvenience caused.
CRIS-Team Scopus Importer:2024-09-09